Determinants of Purchasing Decisions for Kopi Janji Jiwa in Sidoarjo: The Role of Digital Marketing and e-WOM - Noverta Sabela; Siti Aminah (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Advancements in digital technology have driven significant changes in marketing activities, particularly in the food and beverage sector. Digital marketing has become a strategic approach that enables companies to reach consumers more broadly and effectively, while electronic word-of-mouth (e-WOM) facilitates the exchange of information and consumer experiences that can influence purchasing decisions. This study aims to analyze the effect of digital marketing and E-WOM on the purchase decisions of Kopi Janji Jiwa in Sidoarjo, motivated by the phenomenon of declining Top Brand Index scores amid increasingly intense competition in the coffee shop industry. This study employed a quantitative approach using purposive sampling technique involving 110 respondents who had purchased Kopi Janji Jiwa more than once and were residents of Sidoarjo. Most respondents were consumers aged 17–22 years who actively used social media, making them more responsive to digital marketing activities and online information. Data were collected through questionnaires using a Likert scale and analyzed using structural equation modeling-partial least squares (SEM-PLS) with the assistance of the SmartPLS application. The results indicate that digital marketing and e-WOM have a positive and significant effect on the purchase decisions of Kopi Janji Jiwa in Sidoarjo. These findings suggest that effective digital marketing strategies and positive consumer reviews on digital platforms can enhance consumer trust and encourage purchasing decisions. This study provides an empirical contribution to enriching consumer behavior studies, particularly regarding the role of digital marketing and E-WOM in influencing purchasing decisions within the coffee shop industry in Indonesia. Furthermore, the findings can serve as input for companies to optimize digital marketing strategies and manage E-WOM effectively.